(untitled) (Journal of Kidney Cancer, 2022)
Pheochromocytomas are tumors producing catecholamines that arise from chromaffin cells in the adrenal medulla. They are usually benign in multiple endocrine neoplasia type 2 (MEN2) syndrome, but they tend to present bilaterally in 50–80% of the patients. Few researchers have reported success with simultaneous laparoscopic bilateral adrenalectomy. Hence, we report a 48-year-old woman who presented with a panic attack, headache, and abdominal discomfort that had started 10 years ago. The computed tomography (CT) scan showed a large bilateral cystic lesion in both adrenal glands in favor of pheochromocytomas (30 × 22 mm and 18 × 15 mm on the right side and 40 × 33 mm and 35 × 28 mm on the left side). The patient underwent bilateral laparoscopic adrenalectomy without intraoperative or postoperative complications. The total blood loss was 50 cc, and the operative time was 4 h. The histopathology of the specimen revealed pheochromocytomas of adrenal masses. In conclusion, our case demonstrates that synchronized laparoscopic bilateral adrenalectomy can be a safe and feasible treatment option for pheochromocytomas in MEN2 patients.